DAKWAH PERSUASIF (SEBUAH TINJAUAN DARI ASPEK HAKIKAT ROHANIAH) - Amrullah Amrullah (UIN Antasari Banjarmasin, 2017)
Humans are created from two elements, namely, physical (physical) and spiritual (psychic). Therefore man is the perfect being from various aspects of it spiritually (psychologically). Since man has been created perfectly, he has three spiritual powers: al-fikr, al-wijdaan, al-madhadah with different shades, levels and levels between individual human beings; which is expressed in the form of attitudes and behaviors as a result of efforts to meet their psychological needs. In conjunction with persuasive devotion, a da'i must understand and be aware of the spiritual potential of human being as well as object of delivery of message of dakwah, which of course must be supported by skill and skill that exist in da'i self. One of the most basic is where da'i have to master the linguistic of various aspects, so that what is conveyed is not contradictory or in line with the spiritual nature of human beings as mad'u.